Multifunctional Core-Shell Microgels as Pd-Nanoparticle Containing Nanoreactors With Enhanced Catalytic Turnover - Sabadasch, Viktor; Dirksen, Maxim; Fandrich, Pascal; Hellweg, Thomas (Frontiers in Chemistry, 2022)
In this work we present core-shell microgels with tailor-made architecture and properties for the incorporation of palladium nanoparticles. While the microgel core consists of poly-N-isopropylacrylamide (PNIPAM) copolymerized with methacrylic acid (MAc), to obtain an optimal incorporation of palladium nanoparticles, the shell was prepared by copolymerization of NIPAM and the UV-sensitive comonomer 2-hydroxy-4-(methacryloyloxy)-benzophenone (HMABP). The obtained core-shell architecture was analyzed by means of photon correlation spectroscopy, while the incorporated amount of HMABP was further confirmed via Fourier transform infrared spectroscopy. Subsequently, the microgel system was used for loading with palladium nanoparticles and their size and localization were investigated by transmission electron microscopy. The catalytic activity of the monodispers palladium nanoparticles was tested by reduction of 4-nitrophenol to 4-aminophenol. The obtained reaction rate constants for the core-shell system showed enhanced activity compared to the Pd loaded bare core system. Furthermore, it was possible to recycle the catalyst several times. Analysis via transmission electron microscopy revealed, that the incorporated palladium nanoparticles emerged undamaged after the reaction and subsequent purification process since no aggregation or loss in size was observed.